2019
DOI: 10.1186/s12911-019-0812-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantile-based fecal hemoglobin concentration for assessing colorectal neoplasms with 1,263,717 Taiwanese screenees

Abstract: Background Although fecal hemoglobin concentration (f-Hb) was highly associated with the risk of colorectal neoplasms, current studies on this subject are hampered by skewedness of the data and the ordinal property of f-Hb has not been well studied yet. Our aim was to develop a quantile-based method to estimate adjusted percentiles (median) of fecal hemoglobin concentration and their derived prediction for the risk of multistage outcomes of colorectal disease. Methods W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Fecal hemoglobin, a surrogate measure for the presence of blood, is considered a reliable predictor of advanced colorectal neoplasia (Garcia et al, 2015;Navarro et al, 2019;Peng et al, 2019). Here we demonstrated that fecal Hb decreased significantly in mice supplemented AZD3241 vs mice treated with DSS alone, once again aligning with the concomitant preservation of colon surface epithelium and diminished rectal bleeding observed for the same mice.…”
Section: Discussionsupporting
confidence: 69%
“…Fecal hemoglobin, a surrogate measure for the presence of blood, is considered a reliable predictor of advanced colorectal neoplasia (Garcia et al, 2015;Navarro et al, 2019;Peng et al, 2019). Here we demonstrated that fecal Hb decreased significantly in mice supplemented AZD3241 vs mice treated with DSS alone, once again aligning with the concomitant preservation of colon surface epithelium and diminished rectal bleeding observed for the same mice.…”
Section: Discussionsupporting
confidence: 69%
“…Several studies have shown that faecal haemoglobin (Hb) concentrations in previous screening rounds are highly predictive for future detection of advanced neoplasia. 39 , 40 , 41 , 42 , 43 , 44 Individuals who tested just below the cut‐off for a positive test had an 8 to 38 higher odds or hazard of being detected with advanced neoplasia vs those without any detectable Hb, depending on the cut‐off used. The lower estimate comes from a study using a 10 μg Hb/g faeces cut‐off, while in the study with the higher estimate a cut‐off of 80 μg Hb/g faeces was used.…”
Section: Possibilities For Risk‐based Screeningmentioning
confidence: 99%